Produtividade da roseira sob diferentes níveis de irrigação, volumes de substrato e número de drenos por vaso - Alves, Alexandre Maia (2006)
The cultivation of roses (roses sp) is characterized by its high profitability, in comparison with traditional cultivations, however, the handling and the powder-crop demand from the producer perfect technical knowledge. For its time, several employed techniques in the handling in the culture have if characterized by its empiricism, being needed studies. With the objective of presenting suggestions to the producers for a handling hydric, substratum volume and number of appropriate drains for vase adapted, this work was elaborated through two experiments where the effects of those factors were analyzed upon the productivity of the rosebush, in a protected atmosphere. The experiments were conducted in the Reijers Company, in the municipal district of São Benedito-CE. In the first experiment, using experimental maping in blocks at random, five techniques were used (irrigation levels corresponding to 60%, 80%, 100%, 120% and 140% of the evaporation measured in the tank class "A", ECA), all processes were conducted four times. The conclusions were obtained: the use of the tank Class "A" in the handling of irrigation of roses is viable for the producer, because it makes possible the obtaining high productivities; the application of higher volumes of water by the producers reduces the number of stems of 50cm, 60cm and the total production per vase. In the second experiment, using factorial experimental maping 3 x 2, where were analyzed the effects of three substratum volumes (3, 4 and 6 liters for plant) and of two types of vases with 1 and 8 drains, over the number of stems per vase of the rosebush, in a protected atmosphere. The following conclusions were obtained: the smallest substratum volumes for plant provide a larger number of stems per vase, but with prevalence of stems of smaller commercial value. On the contrary, the use of larger substratum volumes per plant by for the producer results in a smaller number of stems per vase, but in a larger number of stems of larger commercial value. The use of vases with a larger number of drain by producer, reduces the total number of stems for vase. For a larger production of stems in vases of 12 L, the producer of rosebushes should plant three plants (4 liters of substratum for plant) in vases with a single drain